2018
DOI: 10.1080/14647273.2018.1504325
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of idiopathic asthenozoospermia as a cause of male infertility

Abstract: Infertility is a worldwide problem affecting about 15% of couples trying to conceive. Asthenozoospermia (AZS) is one of the major causes of male infertility, diagnosed by reduced sperm motility, and has no effective therapeutic treatment. To date, a few genes have been found to be associated with AZS in humans and mice, but in most of cases its molecular aetiology remains unknown. Genetic causes of AZS may include chromosomal abnormalities, specific mutations of nuclear and mitochondrial genes. However recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 160 publications
0
34
0
1
Order By: Relevance
“…Asthenozoospermia, defined by the absence or reduction of sperm motility, is observed in nearly 80% of male infertility cases, either alone or in association with other sperm defects 1 . This pathophysiological condition is induced by structural defects of the sperm flagellum and/or functional alterations impairing flagellar beating and sperm progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthenozoospermia, defined by the absence or reduction of sperm motility, is observed in nearly 80% of male infertility cases, either alone or in association with other sperm defects 1 . This pathophysiological condition is induced by structural defects of the sperm flagellum and/or functional alterations impairing flagellar beating and sperm progression.…”
Section: Introductionmentioning
confidence: 99%
“…1, 7,8 Importantly, asthenozoospermia is also detected in the complete absence of morphological defects, suggesting the involvement of functional defects in activation and/or regulation of flagellar beating. To date, such cases of functional asthenozoospermia remain poorly characterized, and only a few mutations were identified in genes encoding for proteins with enzymatic properties ( GALNTL5 ), seminal components ( SEMG1 ) and ion channels ( CATSPER1‐2‐ε , SLC26A3 , VDAC2 ) 1,9‐12 . Overall, the knowledge obtained by studying those sperm pathological phenotypes provides evidence that, in addition to proper morphology and structure, sperm fertilization potential relies on proper activation of the signalling pathways regulating motility, metabolism and energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Primer infertilite, en az bir yıl süre ile korunmadan, düzenli cinsel ilişkiye rağmen gebelik oluşmaması olarak tanımlanır (1). İnfertil çiftlerin yaklaşık yarısında erkek faktörleri etkili, yaklaşık %15'inde kadın ve erkek faktörleri birlikte görülür (2). Erkek infertilitesi genellikle oligozoospermi, düşük sperm motilitesi ve morfolojik anormallikler nedeniyle ortaya çıkar (3).…”
Section: Introductionunclassified
“…[ 47 ] AZS can not just be considered as a simple condition in isolated diseases, on the contrary, it is always associated with a comprehensive symptom. [ 48 ] Hence, patients with AZS represent a very diverse group actually, and treating this particular patient group is not an easy task. Some scholars found that food supplements may improve seminal fluid conditions by providing energy to male germ cells and protecting these cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%